NONCONVENTIONAL GEOPOLYMERIZATION AND DENSIFICATION METHOD OF ALUMINA-SILICATE WASTE SOLIDS FOR PRODUCING EXTREMELY HIGH-STRENGTH GEOPOLYMERS (Nonconventional Technologies Review, 2024)
Simultaneous geopolymerization and densification of geopolymeric products is a viable process by cold sintering of residual alumina-silicate. The procedure peculiarity is the axial pressing of the powder previously produced by the usual geopolymerization. Sodium metasilicate nonahydrate is the type of alkaline activator used in the experiment, which does not require the addition of water and does not lead to the formation of a suspension. The geopolymer manufacturing process involved a mixture composed of coal ash, ground metallurgical slag, nano-silica, and sodium metasilicate nonahydrate, the pressing force of the powder being between 60-90 MPa. The compression resistance of the geopolymer reached a maximum of 51.75 MPa.
Keywords: cold sintering; geopolymerization; densification; fly ash; slag; strength